Spin-off and efficiency in Islamic banks: DEA approach - Nabilah Nabilah; Mohammad Nur Rianto Al Arif (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to analyze the efficiency level of Islamic banks from spin-off and non-spinoff results and the impact of the separation policy and other factors that affect the efficiency level of Islamic banks.Methodology – This study uses a quantitative approach through data envelopment analysis to measure the efficiency level of Islamic banks and the difference-in-difference approach to examine the impact of separation and other factors that affect the efficiency level of Islamic banks. Data is collected directly from each of the six Islamic banks' financial statements.Findings – The results showed no difference in the efficiency level between before and after the spin-off policy at the spin-off bank. Furthermore, it was found that the efficiency level of spin-off Islamic banks was significantly lower than that of non-spinoff Islamic banks. Implication – This result implies that the rules regarding spin-offs should be evaluated. The spin-off policy must be a corporate action and not a regulation imposed by the regulator. Merger or conversion between sharia business units can be an alternative to improve the performance of sharia banking in Indonesia. Originality – Research on the impact of Islamic bank spin-off policies is still limited. Only a few studies analyze the efficiency level of Islamic banks as a result of spin-offs by measuring data analysis. Therefore, this research will contribute to research that discusses the spin-off policy of Islamic banks, especially the impact on efficiency and the factors that affect the level of efficiency.